+0  
 
+2
118
1
avatar

6t

         ---    = ?

t^-4

Guest Feb 8, 2018

Best Answer 

 #1
avatar
+1

6t / t^-4 =6t x t^4 =6t^(1+4) =6t^5

Guest Feb 8, 2018
 #1
avatar
+1
Best Answer

6t / t^-4 =6t x t^4 =6t^(1+4) =6t^5

Guest Feb 8, 2018

11 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.